A study on the relationship between teamwork and employees' job performance at Telekom Malaysia Berhad, Kuantan Pahang / Noor Fazlina Rosaidi - Rosaidi, Noor Fazlina (2016)
The purpose of this research was to study the relationship between teamwork and employees' job performance at TM using three factors. These three factors were team trust, interdependence and reward and recognition. Objective of this research was to identify the factor of teamwork that will affects on employees' job performance. Method used for this study was correlation research. This is because correlational research was to examine the relationship between the variables. Simple random sampling was used as sampling technique with 52 respondents of sample size at the Telekom Malaysia Berhad (TM) Kuantan, Pahang. The data was collected by the questionnaire to the employees who were working at TM. The result shows that all the factors of the teamwork have significant relationship between employees' job performance and the most influential factor of teamwork was interdependence.